2011
DOI: 10.1186/1477-5751-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of tuberculosis: the experience at a specialized diagnostic laboratory

Abstract: This work describes the experience at a tuberculosis clinical laboratory where relatively new TB diagnosis technologies; nucleic acid detection of two target strands, IS6110 and devR, by PCR and microscopic observation drug susceptibility (MODS) were used. The LJ culture was the gold standard. This evaluation was done from August 2007 to July 2009 on 463 sputum samples of tuberculosis suspects at a specialized tuberculosis clinic in Delhi, India.None of the tests we evaluated can accurately detect the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We did not perform a similar sub-analysis for the MODS because the publications were inadequate for the analysis. Instead, we performed a sub-group analysis, excluding the outlier study which had reported what the authors decsribed as “ unexplained observed disturbing inconsistencies in results”, when they used the MODS for diagnosis of smear-negative TB [ 40 ]. Pooled sensitivity of MODS increased from 73% to 82%, and specificity increased from 91% to 95%.…”
Section: Resultsmentioning
confidence: 99%
“…We did not perform a similar sub-analysis for the MODS because the publications were inadequate for the analysis. Instead, we performed a sub-group analysis, excluding the outlier study which had reported what the authors decsribed as “ unexplained observed disturbing inconsistencies in results”, when they used the MODS for diagnosis of smear-negative TB [ 40 ]. Pooled sensitivity of MODS increased from 73% to 82%, and specificity increased from 91% to 95%.…”
Section: Resultsmentioning
confidence: 99%
“…The reason given was perhaps there is flawed generalization that all pathogenic MTB form cords. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%